Muslim consumer perception towards halal food products in Kota Kinabalu, Sabah / Zulynda Nurain Zamani - Zamani, Zulynda Nurain (2014)
The title of this research is “Muslim Consumer Perception Towards Halal Food Product in Kota Kinabalu, Sabah”. The first purpose of this research is to examine the perception towards halal food product among Muslim in more detail especially in Kota Kinabalu, Sabah. There are four independent variables involved in this research which are Safety, Religious Values, Health and Exclusivity. In order to completing this research, the hypothesis was been constructed and focused on the objective to determine whether there has significant relationship between those independent variables with customer perception. A total of 50 peoples have participated in this study as respondents. The methodology used for the research was primary data collection. For primary data, the researcher was used the method of questionnaire to obtained and collect the information. Thus, the result was been obtained through the analyzing and interpret data of result. The reliability test, frequency analysis, descriptive testing and Pearson’s correlation coefficient testing was used for data analysis. From correlation testing, the result shows that one of the independent variables which is religious values have a strong relationship with customer perception while relationship with the dependent variable with health and safety are moderate and low relationship respectively. For hypothesis, there are clearly shown that all of the hypothesis including safety, religious values and health are supported.